Understanding the Dynamics of Risk Sharing and Performance-Based Compensation in Professional Workplaces: Bridging The Theory and The Practice - Eri Kusnanto; Yessica Amelia; Grace Yulianti (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This qualitative literature review investigates the dynamics of risk sharing and performance-based compensation (PBC) in professional workplaces, aiming to bridge the gap between theoretical frameworks and practical applications. By analyzing existing literature, the review reveals that PBC can effectively align employee incentives with organizational goals, enhancing performance and commitment. However, the success of these systems hinges on various factors, including transparent evaluation processes, equitable risk distribution, and the relevance of performance metrics. The findings highlight that while risk-sharing models can drive long-term engagement, they may also expose employees to financial uncertainties, particularly in volatile industries. Moreover, perceptions of fairness and equity in compensation structures play a crucial role in influencing employee motivation and satisfaction. The review emphasizes the necessity for organizations to carefully design PBC systems that consider industry-specific characteristics and employee preferences to mitigate potential adverse effects. Overall, this research contributes to a deeper understanding of the complexities surrounding PBC and risk sharing, paving the way for future studies to explore their implications in diverse contexts.